Depression and anxiety among sexual minorities in Iceland - Geir Andersen 1994- (2020)
Depressive symptoms and anxiety symptoms are significantly higher among non-heterosexual individuals compared to heterosexual individuals. Scholars have suggested that this is due to increased stressful social environment that non-heterosexual individuals experience. The current study aimed to explore the difference in depressive and anxiety symptoms between non-heterosexual adolescents and heterosexual adolescents in Iceland. The role of parental social support, peer social support and the experience of sexual abuse were examined as contributors to a higher level of depressive symptoms and anxiety symptoms among non-heterosexual individuals. Results indicated that the non-heterosexual adolescents showed significantly more depressive symptoms and anxiety symptoms compared to their heterosexual peers. Non-heterosexual adolescents were more likely to have experienced sexual abuse and they also experienced lower parental social support compared to their heterosexual peers. Regression analysis showed that higher levels of depressive symptoms and anxiety symptoms among the non-heterosexual sample was only significant when there was no history of sexual abuse. Results are discussed from a theoretical perspective. Longitudinal studies on the development of different sexual attraction patterns are suggested for future research. Þunglyndis- og kvíðaeinkenni eru mun hærri meðal þeirra sem skilgreina sig sem hinsegin einstaklinga samanborið við þá sem skilgreina sig sem gagnkynhneigða einstaklinga. Rannsakendur hafa lagt fram þá tilgátu að þessi munur á andlegri heilsu stafi af lakara félagslegu umhverfi sem hinsegin einstaklingar upplifa samanborið við gagnkynhneigða. Þessari rannsókn er ætlað að rannsaka muninn í þunglyndis- og kvíðaeinkennum milli hinsegin unglinga og gagnkynhneigðra unglinga. Áhrif foreldrastuðnings, vinastuðnings og saga um kynferðislegt ofbeldi á þunglyndis- og kvíðaeinkenni meðal hinsegin unglinga voru skoðuð. Niðurstöður leiddu í ljós að hinsegin unglingar sýndu meiri þunglyndis- og kvíðaeinkenni ...